Isolation of chemical compounds and antibacterial activity from the bark of Alphonsea Cylindrica - Munirah Abdul Talip (N/A, 2017)
Isolation of chemical compounds and antibacterial activity from the bark of Alphonsea Cylindrica by Munirah Abdul Talip